Molecular characterization of the effects of heat shock on the infection cycle progression and productivity of the baculovirus expression vector system - Enrique Paz-Cortés; Ana Ruth Pastor; Roberta Salinas-Marín; Octavio T. Ramírez; Laura A. Palomares (PLoS ONE, 2025)
Baculoviruses are widely utilized in biotechnology for various purposes, including recombinant protein expression, antigen presentation, vaccine production, as biopesticides, and as gene therapy vectors. The productivity of the baculovirus expression vector system (BEVS) is significantly affected by the condition of the host cell. However, the impact of host cell stress on the complex baculovirus infection cycle remains not fully understood. This study examines the effects of three gradual heat shock treatments on the production of recombinant protein and viral titers in Sf9 cells (Spodoptera frugiperda) infected with a recombinant baculovirus AcMNPV with fluorescent reporters under late (vp39) and very late (polh) promoters. The heat shock regimens applied before infection were 30°C for 2.5 hours, 37°C for 2.5 hours, and constant 30°C, combined with prostaglandin A1 (PGA1) to enhance the cellular stress response. Significant differences in viral progeny and baculovirus genome replication were observed. Notably, a constant 30°C heat shock increased early viral titers but decreased late-stage yields. Using flow cytometry, we monitored the signal from the two fluorescent reporters and found that some heat shock conditions differentially accelerated or increased their timing or expression levels, with different patterns for each reporter. Additionally we identified, cloned, and sequenced two inducible HSP70 genes from S. frugiperda to track their expression throughout infection, providing insights into the cell’s stress response and the effect of PGA1. These findings suggest that modulating the host heat-shock response can improve baculovirus production and offer insights into the host-virus relationship for new elements or strategies to improve BEVS productivity.